Global Irradiation in Children Treated for Hydrocephalus and Its Change over Time-A Single Institutional Analysis - Lukas Schabl; Julia Küppers; Tobias Jhala; Hermann Winicker; Peter Esslinger; Markus Lehner (MDPI AG, 2022)
Radiation exposure early in life is associated with greater incidences of malignancy. Our goal was to quantify radiation exposure in shunt-treated hydrocephalus patients and study changes in the diagnostic modalities used. A single-center, retrospective analysis was performed, and 41 children treated for hydrocephalus using an adjustable ventriculoperitoneal shunt were identified. Diagnostics associated with hydrocephalus and other comorbidities were analyzed and radiation exposure was calculated. During 330.09 total shunt years, patients were exposed to a mean hydrocephalus-associated radiation dose of 3.93 mSv (range: 0-24.38 mSv), which amounted to a mean rate of 0.49 mSv per shunt year, respectively. Radiation exposure was greatest after shunt insertion in the first year of life. A continuous change from CT scans to MRIs could be seen over the study period, such that patients who underwent shunt insertion after 2017 were not exposed to additional hydrocephalus-associated radiation during their first year of life. Nevertheless, our patients, and a few individuals especially, seemed to be at higher risk for radiation sequelae. Our results suggest that CT scans should be substituted with MRIs, which decrease overall radiation exposure and can lead to zero additional radiation exposure during the first year of life after shunt insertion.